METHOD FOR EFFECTIVE SEPARATION OF MICROPLASTIC PARTICLES FROM BOTTOM SEDIMENTS - V.O. Iemelianov; Ye.І. Nasiedkіn; T.S. Kukovska; S.M. Dovbysh (Геологія і корисні копалини Світового океану)
The study of the distribution of microplastics in the geological component of marine ecosystems, in particular, the detection of the amount of pollution by plastic material, the determination of its types, origin and routes of movement is a relevant direction of research of the scientific world community in recent decades. The SSI "MorGeoEcoCenter of the National Academy of Sciences of Ukraine" within the framework of the international project "Developing Optimal and Open Research Support" for the Black Sea (DOORS) (https://www.doorsblacksea.eu/) conducts research on the distribution of microplastics in the bottom sediments of the shelf areas of the western parts, as well as coastal deposits of the northwestern part of the Black Sea. An important component of the research is the process of sample preparation for laboratory analyses, which determines the qualitative extraction of microplastic particles with preserved shape and size from the mass of bottom sediments. The practice of microplastic’s research in the laboratory of SSI "MorGeoEcoCenter" made it possible to develop equipment for non-contact mixing of bottom sediment samples. The experimental separator created on the basis of a grinding machine allows continuous mixing of sediments, ensuring constant movement of the container with the substance in the horizontal plane and its permanent oscillations with an optimal frequency in the vertical. The non-destructive physical characteristics of oscillations allow the unlimited use of the device for the term that is necessary for the reliable separation of the mass of the bottom sediments of the sample into particles that are unitary in nature and their effective separation by density characteristics in the solution. The size of the grinding platform and the availability of additional elements guarantee the ability to work with containers of various volumes, shapes, and sizes. Further special experimental studies will determine the degree of efficiency of the device and open up the possibility of its involvement in practical work to improve the efficiency of laboratory processing of natural substances and improve the quality of research results.